Social Sector Reform in Transition Countries - Keller, Christian (IMF Working Papers; Working Paper, 2001)
During the transition process, many existing social sector institutions and policies were significantly eroded and their underlying character changed. As a result, they often do not redistribute to the poorest, nor generally serve the role of facilitating economic change. Social sector reforms have therefore become necessary for reasons of social welfare as well as economic growth. The analysis of eleven transition countries-comprising some of the most advanced as well as some of the poorest transition economies-shows that almost all countries have started to undertake reforms; however, their individual efforts vary. Reform does not only stand for cutting back, but also requires in some cases a building up and in others a redesign of social safety nets; it needs to address insurance issues, budgetary transfer programs, the performance of the health and education sector, as well as the labor market regime and the approach to tax administration.